Anti-Obesity Effect of Probiotic Carrot Nectar Incorporated with L. Plantarum MCC5231 - Aditi Goel; Md Touseef Khan; S. P. Muthukumar; Attar Singh Chauhan; Jyoti Prakash Tamang; Prakash. M. Halami (Probiotics and Antimicrobial Proteins, 2026)

Comment on “Effects of Ureaplasma urealyticum infection in human genital tract on sperm DNA and semen quality in male patients” - S Dhanya Dedeepya; Vaishali Goel; Nivedita Nikhil Desai (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Development of floatable composite alginate hydrogel beads for the concentration of anthocyanins and their further characterization - Rajat Goel; Somnath Basak; Rekha S. Singhal (Food and Humanity, 2025)

A review of the current status of biological effects of plant-derived therapeutics in breast cancer - Shantanu Pachal; Hitesh Kumar; Rupshee Jain; Bhawna Goel; Sharyu Kesharwani; Siddharth S. Kesharwani; Vikas Jain (Molecular Biology Reports, 2025)

Comment on “High-resolution modeling of extreme heat events with socioeconomic consideration: a real-case WRF–LES approach” - S. Dhanya Dedeepya; Vaishali Goel; Nivedita Nikhil Desai (Environmental Science and Pollution Research, 2025)

The natural products magnetic resonance database (NP-MRD): comprehensive resource for natural products NMR data enabling discovery and understanding - John R. Cort; Jessica L. Bade; Roger G. Linington; Matthew Pin; Ella F. Poynton; Lloyd W. Sumner; James T. Koller; Zachary M. Tretter; Bharat Goel; David S. Wishart; Vasuk Gautam; Scott McKay; et al. (Phytochemistry Letters, 2025)

HPTLC and LCMS based investigation of ethanolic leaf extracts of Nerium oleander and identification of quercetin as potent compound targeting plasmodium proteases: An analytical and in silico approach - Rajesh Tiwari; Mohammad Khalid Parvez; M.Arockia Babu; Mohammed S. Al-Dosari; Thakur Gurjeet Singh; Kapil Kumar Goel; Nemat Ali; Yogita Tyagi; Umesh Yadav; Bhupinder Kumar; Nisha Bansal (South African Journal of Botany, 2025)

Innovations in tannery wastewater management: a review of zero liquid discharge technology - A. Pundir; M. S. Thakur; B. Goel; Radha; A. Kumar; S. Prakash; M. Thakur; M. Kumar (International Journal of Environmental Science and Technology, 2025)

Evaluation of environmental impacts of mobile phones in India using life cycle assessment technique - D. Dutta; VR. Sankar Cheela; B. Dubey; S. Kumar; S. Goel (International Journal of Environmental Science and Technology, 2025)

Predicting nickel catalyst deactivation in biogas steam and dry reforming for hydrogen production using machine learning - Arsh Kumbhat; Aryan Madaan; Rhythm Goel; Srinivas Appari; Ahmed S. Al-Fatesh; Ahmed I. Osman (Process Safety and Environmental Protection, 2024)

Estimating soil mineral nitrogen from data-sparse field experiments using crop model-guided deep learning approach - Rishabh Gupta; Satya K. Pothapragada; Weihuang Xu; Prateek Kumar Goel; Miguel A. Barrera; Mira S. Saldanha; Joel B. Harley; Kelly T. Morgan; Alina Zare; Lincoln Zotarelli (Computers and Electronics in Agriculture, 2024)

A multi-label dataset and its evaluation for automated scoring system for cleanliness assessment in video capsule endoscopy - Palak Handa; Nidhi Goel; S. Indu; Deepak Gunjan (Physical and Engineering Sciences in Medicine, 2024)

Remediation of dye wastewater using radiation-functionalized polyurethane foam: A viable waste to wealth conversion strategy - N. K. Goel; N. Misra; S. A. Shelkar; S. Rawat; V. Kumar (International Journal of Environmental Science and Technology, 2024)

Trichoderma Mediated Metal Chelator and Its Role in Solanum melongena Growth Under Heavy Metals - Gaurav Yadav; Neha Sharma; Arti Goel; Ajit Varma; Arti Mishra; S. L. Kothari; D. K. Choudhary (Journal of Plant Growth Regulation, 2024)

Evidence-Based Therapeutic Potential of Natural Seed Oil of Desert Date/Ingudi (Balanites aegyptiaca Linn. Delile) in Chronic Diabetic Wound - Sanjeev Kumar; Anurag Mishra; Kamal Nayan Dwivedi; Neelu Singh; Abhishek Kumar; Satyanam Kumar Bhartiya; S. Krishnamoorthi; Amit Kumar; Bharat Goel; Shreyans K. Jain (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2023)

Biotransformation of 2,4,6-trinitrotoluene by Diaphorobacter sp. strain DS2 - Swati Gupta; Shikhar S Goel; Gurunath Ramanathan; Zeev Ronen (Environmental Science and Pollution Research, 2023)

Reassessing the availability of crop residue as a bioenergy resource in India: A field-survey based study - Taveen S. Kapoor; Chimurkar Navinya; Gupta Anurag; Pradnya Lokhande; Shubham Rathi; Anubha Goel; Renuka Sharma; Rahul Arya; Tuhin K. Mandal; K.P. Jithin; Shiva Nagendra; Mohd Imran; et al. (Journal of Environmental Management, 2023)

Site-specific characterisation of hydrogeological parameters for low-level solid radioactive waste disposal facility at Tarapur, India - Shelly Goel; Manish Chopra; Aditi C Patra; Faby Sunny; G Ganesh; R B Oza; M S Kulkarni (Journal of Earth System Science, 2023)

Different GCMs yet similar outcome: predicting the habitat distribution of Shorea robusta C.F. Gaertn. in the Indian Himalayas using CMIP5 and CMIP6 climate models - Sharanjeet Kaur; Siddhartha Kaushal; Dibyendu Adhikari; Krishna Raj; K. S. Rao; Rajesh Tandon; Shailendra Goel; Saroj K. Barik; Ratul Baishya (Environmental Monitoring and Assessment, 2023)

Transformation of 2, 4, 6-trinitrotoluene by Stenotrophomonas strain SG1 under aerobic and anaerobic conditions - Swati Gupta; Shikhar S Goel; Hagar Siebner; Zeev Ronen; Gurunath Ramanathan (Chemosphere, 2023)

Evaluation of biochemical responses in pepper genotypes inoculated with Pepper leaf curl virus - Neeraj Dwivedi; Leena Johny; Mayurika Goel; Dipti S. Tirkey (Indian Phytopathology, 2022)

Plasma polymerized functional supermagnetic Fe3O4 nanostructured templates for laccase immobilization: A robust catalytic system for bio-inspired dye degradation - Swarnima Rawat; Nilanjal Misra; Sher Singh Meena; Shubhangi S. Shelkar; Naveen Kumar N; Narender Kumar Goel; Virendra Kumar (Environmental Science and Pollution Research, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Identification of Drought-Tolerant Co-canes Based on Physiological Traits, Yield Attributes and Drought Tolerance Indices - Pooja Dhansu; Neeraj Kulshreshtha; Ravinder Kumar; Arun K. Raja; S. K. Pandey; Vishal Goel; Bakshi Ram (Sugar Tech, 2021)

Assessment of Soil Chemical Quality, Soil Microbial Population and Plant Growth Parameters Under Organic and Conventional Rice–Wheat Cropping System - Reeta Goel; Prasenjit Debbarma; Puja Kumari; Deep Chandra Suyal; Saurabh Kumar; B. S. Mahapatra (Agricultural Research, 2021)

Dispersal limitation and fire feedbacks maintain mesic savannas in Madagascar - Nikunj Goel; Erik S. Van Vleck; Julie C. Aleman; A. Carla Staver (Ecology, 2020)
Madagascar is regarded by some as one of the most degraded landscapes on Earth, with estimates suggesting that 90% of forests have been lost to indigenous Tavy farming. However, the extent of this degradation has been challenged: paleoecological data, phylogeographic analysis, and species richness indicate that pyrogenic savannas in central Madagascar predate human arrival, even though rainfall is sufficient to allow forest expansion into central Madagascar. These observations raise a question—if savannas in Madagascar are not anthropogenic, how then are they maintained in regions where the climate can support forest? Observation reveals that the savanna–forest boundary coincides with a dispersal barrier—the escarpment of the Central Plateau. Using a stepping‐stone model, we show that in a limited dispersal landscape, a stable savanna–forest boundary can form because of fire–vegetation feedbacks. This phenomenon, referred to as range pinning, could explain why eastern lowland forests have not expanded into the mesic savannas of the Central Highlands. This work challenges the view that highland savannas in Madagascar are derived by human‐lit fires and, more importantly, suggests that partial dispersal barriers and strong nonlinear feedbacks can pin biogeographical boundaries over a wide range of environmental conditions, providing a temporary buffer against climate change.

Influence of fin density on the performance of an impinging jet with fins type solar air heater - Abhishek Kumar Goel; S. N. Singh (Environment, Development and Sustainability, 2020)

Development of mixed anaerobic culture for degrading high concentrations of chlorophenols - M. Goel; M. Ramesh; J. S. Sudarsan; R. Kanawade; S. Nithiyanantham (International Journal of Environmental Science and Technology, 2020)

Experimental study of heat transfer characteristics of an impinging jet solar air heater with fins - Abhishek Kumar Goel; S. N. Singh (Environment, Development and Sustainability, 2020)

Prediction of upslope movement of Rhododendron arboreum in Western Himalaya - Sri N. S. Veera; Rajendra M. Panda; Mukunda D. Behera; Shailendra Goel; Partha S. Roy; Saroj K. Barik (Tropical Ecology, 2019)

Stability of Vaccines - N. Dumpa; K. Goel; Yuhan Guo; H. McFall; Amit Raviraj Pillai; Ashay Shukla; M. A. Repka; S. Narasimha Murthy (AAPS PharmSciTech, 2019)

Genome-Wide Analysis in Wild and Cultivated Oryza Species Reveals Abundance of NBS Genes in Progenitors of Cultivated Rice - Hukam C. Rawal; S. V. Amitha Mithra; Kirti Arora; Vishesh Kumar; Neha Goel; Dwijesh Chandra Mishra; K. K. Chaturvedi; Anil Rai; S. Vimala Devi; T. R. Sharma; Amolkumar U. Solanke (Plant Molecular Biology Reporter, 2018)

Mortality associated with candidemia in non-neutropenic cancer patients is not less compared to a neutropenic cohort of cancer patients - G. Goel; M. Chandy; A. Bhattacharyya; S. Banerjee; S. Chatterjee; S. Mullick; S. Sinha; K. Sengupta; K. Dhar; S. Bhattacharya; S. Rudramurthy; A. Chakrabarti (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Matrix-assisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF MS) for rapid identification of micro-organisms in the routine clinical microbiology laboratory - C. Wattal; J. K. Oberoi; N. Goel; R. Raveendran; S. Khanna (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

ISSR markers for gender identification and genetic diagnosis of Hippophae rhamnoides ssp. turkestanica growing at high altitudes in Ladakh region (Jammu and Kashmir) - Kamal Das; Showkat Hussain Ganie; Yash Mangla; Tanvir-Ul-Hassan Dar; Manju Chaudhary; Rakesh Kumar Thakur; Rajesh Tandon; S. N. Raina; Shailendra Goel (Protoplasma, 2017)

A novel technique for detoxification of phenol from wastewater: Nanoparticle Assisted Nano Filtration (NANF) - L. D. Naidu; S. Saravanan; Mukesh Goel; S. Periasamy; Pieter Stroeve (Journal of Environmental Health Science and Engineering, 2016)

Development of an efficient, genotype independent plant regeneration and transformation protocol using cotyledonary nodes in safflower (Carthamus tinctorius L.) - V. Patial; R. Krishna; G. Arya; V. K. Singh; M. Agarwal; S. Goel; A. Jagannath; A. Kumar (Journal of Plant Biochemistry and Biotechnology, 2016)

Response of indigenously developed bacterial consortia in progressive degradation of polyvinyl chloride - Mohammad S Anwar; Anil Kapri; Vasvi Chaudhry; Aradhana Mishra; Mohammad W. Ansari; Yogesh Souche; Chandra S. Nautiyal; M. G. H. Zaidi; Reeta Goel (Protoplasma, 2016)

Assessment of genetic diversity in indigenous turmeric (Curcuma longa) germplasm from India using molecular markers - Sushma Verma; Shweta Singh; Suresh Sharma; S. K. Tewari; R. K. Roy; A. K. Goel; T. S. Rana (Physiology and Molecular Biology of Plants, 2015)

Unraveling the cytotoxic potential of Temozolomide loaded into PLGA nanoparticles - Darshana S Jain; Rajani B Athawale; Amrita N Bajaj; Shruti S Shrikhande; Peeyush N Goel; Yuvraj Nikam; Rajiv P Gude (DARU Journal of Pharmaceutical Sciences, 2014)
Background Nanotechnology has received great attention since a decade for the treatment of different varieties of cancer. However, there is a limited data available on the cytotoxic potential of Temozolomide (TMZ) formulations. In the current research work, an attempt has been made to understand the anti-metastatic effect of the drug after loading into PLGA nanoparticles against C6 glioma cells. Nanoparticles were prepared using solvent diffusion method and were characterized for size and morphology. Diffusion of the drug from the nanoparticles was studied by dialysis method. The designed nanoparticles were also assessed for cellular uptake using confocal microscopy and flow cytometry. Results PLGA nanoparticles caused a sustained release of the drug and showed a higher cellular uptake. The drug formulations also affected the cellular proliferation and motility. Conclusion PLGA coated nanoparticles prolong the activity of the loaded drug while retaining the anti-metastatic activity.

Water pollution of Sabarmati River—a Harbinger to potential disaster - Soumya Haldar; Subir Kumar Mandal; R. B. Thorat; Sangita Goel; Krushnakant D. Baxi; Navalsang P. Parmer; Vipul Patel; S. Basha; K. H. Mody (Environmental Monitoring and Assessment, 2014)

In vitro cytogenetic assessment of trichloroacetic acid in human peripheral blood lymphocytes - Meenu Varshney; Abhijit Chandra; L. K. S. Chauhan; S. K. Goel (Environmental Science and Pollution Research, 2014)

Micronucleus induction by oxidative metabolites of trichloroethylene in cultured human peripheral blood lymphocytes: a comparative genotoxicity study - Meenu Varshney; Abhijit Chandra; L. K. S. Chauhan; Sudhir K. Goel (Environmental Science and Pollution Research, 2013)

Is an Alternative Drug Delivery System Needed for Docetaxel? The Role of Controlling Epimerization in Formulations and Beyond - Arehalli S. Manjappa; Peeyush N. Goel; Makam P. Vekataraju; Kesarla S. Rajesh; Kinjal Makwana; Mukesh Ukawala; Yuvraj Nikam; Rajiv P. Gude; Rayasa S. Ramachandra Murthy (Pharmaceutical Research, 2013)

Molecular Characterization of Vibrio cholerae O1 Reveals Continuous Evolution of Its New Variants in India - M. Jain; K. S. Kushwah; P. Kumar; A. K. Goel (Indian Journal of Microbiology, 2013)

Expression of CspE by a Psychrotrophic Bacterium Enterobacter ludwigii PAS1, Isolated from Indian Himalayan Soil and In silico Protein Modelling, Prediction of Conserved Residues and Active Sites - Premalatha Kandasamy; Nidarshana Chaturvedi; Brijesh S. Sisodia; Ajit K. Shasany; Shachi Gahoi; Soma S. Marla; Reeta Goel (Current Microbiology, 2013)

Stage and Discharge Forecasting by SVM and ANN Techniques - S. K. Aggarwal; Arun Goel; Vijay P. Singh (Water Resources Management, 2012)

Genetic structure and diversity of India hybrid tea - S. N. Raina; P. S. Ahuja; R. K. Sharma; S. C. Das; P. Bhardwaj; R. Negi; V. Sharma; S. S. Singh; R. K. Sud; R. K. Kalia; V. Pandey; J. Banik; et al. (Genetic Resources and Crop Evolution, 2012)

Detection of Rotavirus from Hospitalized Diarrheic Children in Uttar Pradesh, India - S. K. Dash; Krishna Kumar; A. Tewari; P. Varshney; A. Goel; A. K. Bhatia (Indian Journal of Microbiology, 2012)

Growth and metabolic responses of maize (C 4 species) and rice (C 3 species) genotypes to cadmium toxicity - S. Goel; J. Malik; R. Awasthi; R. Sandhir; H. Nayyar (Cereal Research Communications, 2012)

Methane mitigation from ruminants using tannins and saponins - Gunjan Goel; Harinder P. S. Makkar (Tropical Animal Health and Production, 2012)

Molecular characterization of a new isolate of phytoplasma associated with malformation and twisting of floral spikes of Gladiolus in India - S. K. Raj; S. K. Snehi; M. S. Khan; M. H. Asif; S. K. Bag; R. K. Roy; A. K. Goel (Journal of General Plant Pathology, 2010)

Overexpression of osmotin gene confers tolerance to salt and drought stresses in transgenic tomato (Solanum lycopersicum L.) - D. Goel; A. K. Singh; V. Yadav; S. B. Babbar; K. C. Bansal (Protoplasma, 2010)

Limitation of 90 m SRTM DEM in drainage network delineation using D8 method—a case study in flat terrain of Bangladesh - M. M. Rahman; D. S. Arya; N. K. Goel (Applied Geomatics, 2010)

Variation of ambient SO2 over Delhi - A. Datta; T. Saud; A. Goel; S. Tiwari; S. K. Sharma; M. Saxena; T. K. Mandal (Journal of Atmospheric Chemistry, 2010)

Development of isopluvial map using L-moment approach for Tehri-Garhwal Himalaya - S. Sarkar; N. K. Goel; B. S. Mathur (Stochastic Environmental Research and Risk Assessment, 2010)

Molecular characterization of Vibrio cholerae outbreak strains with altered El Tor biotype from southern India - A. K. Goel; M. Jain; P. Kumar; S. C. Jiang (World Journal of Microbiology and Biotechnology, 2010)

Exploration of Csp Genes from Temperate and Glacier Soils of the Indian Himalayas and In Silico Analysis of Encoding Proteins - Prema K. Latha; Ravindra Soni; Mahejibin Khan; Soma S. Marla; Reeta Goel (Current Microbiology, 2009)

Analysis of historical changes in rainfall in the Indian Himalayas - Ashoke Basistha; D. S. Arya; N. K. Goel (International Journal of Climatology, 2009)
The present study attempts to explore changes in rainfall pattern in the Indian Himalayas during 20th century using 80‐year data from 30 rain gauge stations maintained by the India Meteorological Department (IMD). Modified Mann–Kendall test (MMK) was applied to detect trend, and Pettitt–Mann–Whitney (PMW) test was employed to detect possible shift. Implication of the change is discussed in terms of percentage change over mean. The results show that the most probable year of change in annual as well as monsoon rainfall in the region is 1964. There was an increasing trend upto 1964 (corroborating with all India and nearby plains), followed by a decreasing trend in 1965–1980 (exclusive to this region). In the entire region, changes are most conspicuous over the Shivaliks and the southern part of the Lesser Himalayas. Copyright © 2008 Royal Meteorological Society

In vitro manipulations in St. John’s wort (Hypericum perforatum L.) for incessant and scale up micropropagation using adventitious roots in liquid medium and assessment of clonal fidelity using RAPD analysis - Manoj K. Goel; A. K. Kukreja; N. S. Bisht (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Assessment of environmental benefits of flyover construction over signalized junctions: a case study - S. K. Goyal; Sangita Goel; S. M. Tamhane (Environmental Monitoring and Assessment, 2009)

Spatial Distribution of Rainfall in Indian Himalayas – A Case Study of Uttarakhand Region - Ashoke Basistha; D. S. Arya; N. K. Goel (Water Resources Management, 2008)

Transfer of leaf rust and stripe rust resistance from Aegilops umbellulata Zhuk. to bread wheat (Triticum aestivum L.) - Parveen Chhuneja; Satinder Kaur; R. K. Goel; M. Aghaee-Sarbarzeh; M. Prashar; H. S. Dhaliwal (Genetic Resources and Crop Evolution, 2008)

Declination of Copper Toxicity in Pigeon Pea and Soil System by Growth-Promoting Proteus vulgaris KNP3 Strain - Anju Rani; Yogesh S. Shouche; Reeta Goel (Current Microbiology, 2008)

Mapping of adult plant stripe rust resistance genes in diploid A genome wheat species and their transfer to bread wheat - Parveen Chhuneja; Satinder Kaur; Tosh Garg; Meenu Ghai; Simarjit Kaur; M. Prashar; N. S. Bains; R. K. Goel; Beat Keller; H. S. Dhaliwal; Kuldeep Singh (Theoretical and Applied Genetics, 2008)

Colorectal cancer screening education, prioritization, and self-perceived preparedness among primary care residents: Data from a national survey - Amy S. Oxentenko; Nisheeth K. Goel; Darrell S. Pardi; Robert A. Vierkant; Wesley O. Petersen; Joseph C. Kolars; Robert T. Flinchbaugh; Timothy O. Wilson; Katherine Sharpe; John H. Bond; Robert A. Smith; Bernard Levin; et al. (Journal of Cancer Education, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Operation analysis of a reservoir in GIS environment using remote sensing inputs - M. K. Goel; P. Kumar; S. K. Jain; R. S. Tiwari (International Journal of Remote Sensing, 2007)

Single multiplex polymerase chain reaction for environmental surveillance of toxigenic—Pathogenic O1 and Non-O1vibrio cholerae - A. K. Goel; S. Ponmariappan; D. V. Kamboj; L. Singh (Folia Microbiologica, 2007)

Characterization of protein transacetylase from human placenta as a signaling molecule calreticulin using polyphenolic peracetates as the acetyl group donors - Seema; Ranju Kumari; Garima Gupta; Daman Saluja; Ajit Kumar; Sanjay Goel; Yogesh K. Tyagi; Ruchika Gulati; Anjali Vinocha; Kambadoor Muralidhar; Bilikere S. Dwarakanth; Ramesh C. Rastogi; et al. (Cell Biochemistry and Biophysics, 2007)

Brackish water subirrigation for vegetables - R. M. Patel; S. O. Prasher; P. K. Goel; C. A. Madramootoo; R. S. Broughton (Irrigation and Drainage, 2003)
As freshwater resources for irrigation are being depleted rapidly, recent emphasis has been on the development of nonconventional water sources: reuse of agricultural drainage water, use of industrial or municipal wastewater, and use of brackish water for irrigation. Experiments conducted in field lysimeters over three seasons sought to investigate the feasibility of using brackish water for growing moderately sensitive crops. Brackish waters, with salinity levels of 1, 5 and 9 dS m −1 , were used. In 1993 the effects of a factorial combination of three subirrigation water salinity levels, two water table depths and four NPK fertilizer combinations on salt buildup in an initially nonsaline soil and on green pepper ( Capsicum annuum L.) performance were assessed. A gradual increase in soil solution salinity (EC sw ) from the water table to the soil surface was evident; however, throughout the growing season, the EC sw did not reach a level that could seriously damage the crop. There was no significant difference in pepper yields due to either salinity of subirrigation water or water table depth. In 1994, two potato ( Solanum tuberosum L.) cultivars were grown in the soil, which was salinized with 3.5 dS m −1 water before planting tubers. The salt buildup pattern was similar to that observed in 1993; however, the EC sw levels were higher in 1994 due to the higher initial soil salinity. Moreover, a decrease in EC sw was observed near the water table in lysimeters subirrigated with 1 dS m −1 water. For both cultivars, no significant difference in tuber yield was observed due to either water table depth or subirrigation water salinity. In 1995, three potato cultivars were grown in a nonsaline soil as well as a soil presalinized with 2 dS m −1 water. In the topsoil layer, higher rate of increase in EC sw was observed in the saline soil compared to the nonsaline soil. No significant difference in total tuber yield was observed due to either the initial soil salinity levels or subirrigation water salinity levels. Brackish water with salinity levels of up to 9 dS m −1 , when applied through subirrigation, could be used to successfully produce green peppers and potatoes under semiarid to arid conditions. Copyright © 2002 John Wiley & Sons, Ltd.

Stimulation of nodulation and plant growth of chickpea ( Cicer arietinum L . ) by Pseudomonas spp. antagonistic to fungal pathogens - Goel A.; Sindhu S.; Dadarwal K. (Biology and Fertility of Soils, 2002)

The ability of an HSV strain to initiate zosteriform spread correlates with its neuroinvasive disease potential - N. Goel; H. Mao; Q. Rong; J. J. Docherty; D. Zimmerman; K. S. Rosenthal (Archives of Virology, 2002)

Physical mapping of 18S-5.8S-26S and 5S ribosomal RNA gene families in three important vetches (Vicia species) and their allied taxa constituting three species complexes - S. N. Raina; Y. Mukai; K. Kawaguchi; S. Goel; A. Jain (Theoretical and Applied Genetics, 2001)

Prophylactic oophorectomy in Ontario - L. Elit; B. Rosen; V. Goel; L. McLaughlin; M. K. F. Fung; J. Shime; S. Narod (Familial Cancer, 2001)

Evidence for new nuclear and mitochondrial genome organizations among high-frequency somatic embryogenesis-derived plants of allotetraploid Coffea arabica L. (Rubiaceae) - V. Rani; K. P. Singh; B. Shiran; S. Nandy; S. Goel; R. M. Devarumath; H. L. Sreenath; S. N. Raina (Plant Cell Reports, 2000)

Attenuation of changes in sarcoplasmic reticular gene expression in cardiac hypertrophy by propranolol and verapamil - Satoshi Takeo; Adel B. Elmoselhi; Raj Goel; Emmanuelle Sentex; Jingwei Wang; Naranjan S. Dhalla (Molecular and Cellular Biochemistry, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Short Communication: Photoinduced sporulation in Trichoderma harzianum–an experimental approach to primary events - R. Gupta; R.K. Saxena; S. Goel (World Journal of Microbiology and Biotechnology, 1997)